2015
DOI: 10.1093/eurheartj/ehv097
|View full text |Cite
|
Sign up to set email alerts
|

Secundum atrial septal defect is associated with reduced survival in adult men

Abstract: In contrast to women, adult men with an ASD2 have worse survival than a sex-matched general population. Male patients also have a greater risk of morbidity during adult life. Sex disparity in survival and morbidity suggests the need for a sex-specific clinical approach towards these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 33 publications
0
12
1
Order By: Relevance
“…The increased mortality in simple CHD lesions reported by Videbaek et al, for example, was also found in a recent study from the Concor registry. 4 Both study designs had important and different limitations, well described in the articles and accompanying editorials, 1,2,4,5 but eventually showed similar results. This is reassuring for the reliability of registry-based results.…”
mentioning
confidence: 82%
“…The increased mortality in simple CHD lesions reported by Videbaek et al, for example, was also found in a recent study from the Concor registry. 4 Both study designs had important and different limitations, well described in the articles and accompanying editorials, 1,2,4,5 but eventually showed similar results. This is reassuring for the reliability of registry-based results.…”
mentioning
confidence: 82%
“…PSI is a cooperation of all eight Dutch University Medical Centers (UMCs) and aims at building large prospectively collected datasets with uniform and standardized storage of biomaterials for complex diseases. Currently, PSI covers 18 disease-specific cohorts called 'Pearls', and this number is still growing [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. PSI is centrally organized and has an executive board for operational management to ensure collective standardization strategies.…”
Section: Project Descriptionmentioning
confidence: 99%
“…Regarding all disease cohorts, the research projects based on PSI data and samples have led to several scientific publications [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]18].…”
Section: Release Datementioning
confidence: 99%
“…In 2007, the Netherlands Federation of University Medical Centers (NFU) launched the Parelsnoer Institute (PSI) [1], with the aim of facilitating medical research and innovation ultimately leading to better diagnosis, treatment or even prevention of complex disorders [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. PSI is a collaborative network of all eight Dutch University Medical Centers (UMCs), also known as academic teaching hospitals.…”
Section: Project Descriptionmentioning
confidence: 99%
“…PSI releases data and samples to research projects on a regular basis. Thus far, the research projects have led to many scientific publications [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Release Datementioning
confidence: 99%